2013
DOI: 10.1371/journal.pone.0075059
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Has Beneficial Effects on Allergen-Induced Airway Inflammation and Hyperreactivity in Mice

Abstract: BackgroundFish oil (FO) is rich in n-3 polyunsaturated fatty acids (PUFA), which have been suggested to be anti-inflammatory and are associated with improvement of several inflammatory diseases. In this study, we investigated the influence of FO on allergen-induced lung inflammation and airway hyperreactivity in mice.MethodsMale A/J mice were fed either a standard-chow (SC) or a FO diet (FO) for 8 weeks. After 4 weeks, each group was further randomized for ovalbumin (SC-OVA and FO-OVA) or saline (SC-SAL and FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 57 publications
(84 reference statements)
2
30
0
Order By: Relevance
“…The most important components of fish oil are the eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids [10]. Fish oil improves IR [11], hepatic steatosis [12,13] and some inflammatory diseases such as asthma [14] and Crohn's disease [15]. The ability of these n-3 PUFAs to be agonists of the PPARs, especially PPARγ, is recognized as one of the mechanisms of their beneficial effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…The most important components of fish oil are the eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids [10]. Fish oil improves IR [11], hepatic steatosis [12,13] and some inflammatory diseases such as asthma [14] and Crohn's disease [15]. The ability of these n-3 PUFAs to be agonists of the PPARs, especially PPARγ, is recognized as one of the mechanisms of their beneficial effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bargut et al’s 12 study demonstrated a significantly reduced eosinophilic response in the OVA-exposed fish oil group when compared to the OVA-exposed control group. Eliaçik et al’s 14 study showed no significant difference in eosinophil concentration ratios between groups.…”
Section: Resultsmentioning
confidence: 93%
“…In Bargut et al’s 12 mice study, results showed a significant reduction in peribronchiolar matrix deposition post-antigen exposure (p = 0.0099). In addition, the use of fish oil reduced antigen-induced lung hyperreactivity (p < 0.05).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, at this stage it is premature to assume that increased IL-5 levels will lead to exacerbated disease. In fact, n-3 PUFAs may have a beneficial role in preventing lung inflammation in asthma and there is even evidence to show that n-3 PUFAs can lower IL-5 levels [25, 26]. …”
Section: Discussionmentioning
confidence: 99%